Association between Single Nucleotide Polymorphisms and Endometriosis in a Brazilian Population - Viana, Paula Coelho Silva; Mendes, Ana Carolina Delgado Malvaccini; Delgado, Lucas Farah; Tostes, Gustavo; Gonçalves, Lidiane; Gonçalves Júnior, Homero; Raposo, Nádia Rezende Barbosa; Vitral, Geraldo Sérgio Farinazzo; Gerheim, Pamela Souza Almeida Silva (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2020)
Objective To investigate the association between genetic polymorphisms in candidate genes or candidate regions and the development of endometriosis in Brazilian women.Methods A total of 30 women between 25 and 64 years old with a diagnosis of endometriosis participated in the present study, as well as 30 matched control women from the same age group, asymptomatic and without family history of the disease. The patients genotypic and allelic frequencies of polymorphisms in the GREB1 gene (rs13394619) and in the intergenic region at position 7p15.2 (rs12700667) were analyzed and compared.Results There was no significant difference in the frequency of genotypes for the A > G polymorphism (rs13394619) in the GREB1 gene between the two groups. However, the distribution frequencies of the genotypes for the A > G polymorphism (rs12700667) in an intergenic region on chromosome 7 were different for control patients and for patients with endometriosis, with higher frequency of the AG genotype compared to the GG between patients with the disease (odds ratio [OR] = 3.49; confidence interval [CI] = 1.47–8.26).Conclusion The present study suggests that the polymorphism in the intergenic region of chromosome 7 is associated with the risk of developing endometriosis in a population of Brazilian women from Juiz de Fora.
Keywords: endometriosis; polymorphism; single nucleotide; genetics